Personal Ethics in a Corporate World - Francis , Ronald D.; Armstrong , Anona (Journal of Law and Governance, 2008)
This paper addresses the relationship between personal morality and ethical corporate behaviour. The main issue addressed here is the positing of the concept of moral intelligence – the relationship of personal moral stance and corporate behaviour. Just as there is intellectual competence (IQ) and emotional intelligence (EIQ), so too there is moral intelligence. This paper outlines the theoretical and practical basis for the case. Mention is made of confounding issues, such as the stability of moral intelligence, the way in which situational context may over-ride it, and how it might be identified in a manner that is economical, reliable, and valid. It is argued that the development of the concept, and a test, has substantial commercial benefits.